The Strategic Planning Process And Current Practices: A Comparative Empirical Study of UMW Toyota Motor And Chemical Company of Malaysia. - Zandi Pour Joopari, GholamReza (2012)
This article focuses on the strategic planning process and its best practices that are applied by companies in general and by two prominent, non-competing companies operating in Malaysia: UMW Toyota Sdn. Bhd. and the Chemical Company of Malaysia-Fertilizers Division (CCMFD), in specific. Applying a comparative qualitative case study research methodology, the major objectives of the study are to investigate in depth the different aspects, processes, personnel, and practices employed by these top, well-known companies for their strategic planning. Using the grounding theory as a framework of analysis, the research findings revealed common as well as distinctive strategic planning practices between the companies under the study. The output of this project is a set of best practices to strategic planning that are followed by UMW Toyota as well as CCMFD. Some of these best practices are found to be related to the flexibility of the strategic plan, formulation via consensus, and continuous follow up through a centralized strategic planning unit. Eventually, studying such topic can help researchers, strategic management students and junior managers in linking theory to practice and understand the process as it is adopted by the strategic planners of these prominent companies within their real business context.